Pemanfaatan Digital Marketing Channel dalam Upaya Memperluas Pemasaran Produk Jahe Merah Instan Sarongge - Argawan, Benjamin; Halim, Budiyanto; Wijaya, Jessica; Ekaputri, Kartika; Aditia, Kevin Christian; Prasetya, Nicolas Rama; Candra, Trivaldi; Yuliati*, Retno (Journal Pemberdayaan Masyarakat Indonesia, 2019)
This paper aims to utilize the Digital Marketing Channel in terms of expanding the marketing of Sarongge Instant Red Ginger. this paper is based on the difficulties that partner’s experience upon doing the marketing and the usage of Digital Marketing Channel, and thus the authors feels that the brand awareness from the product is still very low. as for the reason of utilizing Digital Marketing Channel is aimed to overcomes the weaknesses that happens during the consignment such as the length of product turnover, the lack of network marketing, and the high cost of transportation in product distribution. By having the Digital Marketing Channel, authors finds the solution to resolve those problems by using platforms like Tokopedia, Instagram, and Whatsapp so that the product sales not only concentrated in the Cipanas area. With the use of Digital Marketing Channel, it is evident that the sales of Sarongge Instant Red Ginger increases by 66% and the products can be purchased by the community anytime.